Pengaruh Kecemasan Menghadapi Pemutusan Hubungan Kerja terhadap Motivasi Kerja Karyawan PT X di Kota Salatiga - Yuliana Widyantari; Susana Prapunoto; A. Ign. Kristijanto (Universitas Negeri Medan, 2020)
This study aims to determine the effect of anxiety facing work termination on employee motivation at PT X Salatiga. The sample in this study amounted to 73 respondents who are still active employees working at PT X. The sampling technique is done by simple random sampling. Data collection uses a psychological scale that is the scale of work motivation based on Abraham Maslow's motivation theory and anxiety facing retirement scale based on the theory put forward by Oluseyi & Olufemi. The data used are primary data analyzed using a simple linear regression test. The results showed that anxiety facing work termination affects work motivation by 26.8% while the remaining 73.2% is influenced by other variables not examined. The researcher can then study based on age, position and also examine other variables that are factors of work motivation, for example marital status between married employees compared to employees who have not married, the length of service of employees in a company.